Family functioning in the Mozambican context: Results of a psychometric study of the SCORE‐15 scale. Issue 2 (15th September 2022) - Bié, Domingos; Narciso, Isabel; Crespo, Carla; Roberto, Magda
Abstract: The Systemic Clinical Outcome and Routine Evaluation (SCORE)‐15 scale is a widely used tool for measuring family functioning across three dimensions: strengths and adaptability, overwhelmed by difficulties, and disrupted communication. This study assessed the factorial validity and reliability of the SCORE‐15 in the Mozambican context. Four‐hundred university students completed the SCORE‐15 scale and the depression, anxiety and hostility subscales of the Brief Symptom Inventory (BSI). The confirmatory factor analysis supported a three‐factor structure that presented adequate model fit and reliability indexes. Poorer family functioning was correlated with psychopathological symptoms, except for the association between depression and disrupted communication. Women revealed higher levels of disrupted communication, while being single was associated with lower levels of being overwhelmed by difficulties and disrupted communication. Age was positively associated with being overwhelmed by difficulties and disrupted communication. The Mozambican version of the SCORE‐15 showed good factorial validity and reliability and can be used in this national diverse socio‐cultural context. Practitioner points SCORE‐15 is a systemic self‐report measure for routine clinical use and research on family relationships. In this study, SCORE‐15 showed evidence of reliability and validity in Mozambique. Abstract : Resumen: La escala Systemic Clinical Outcome and Routine Evaluation (SCORE)‐15 es una herramienta ampliamente utilizada para medir el funcionamiento familiar en tres dimensiones: (1) fortalezas y adaptabilidad, (2) sobrepasado por las dificultades y (3) comunicación disruptiva. Este estudio evaluó la validez factorial y la fiabilidad del SCORE‐15 en el contexto mozambiqueño. Cuatrocientos estudiantes universitarios completaron la escala SCORE‐15 y las subescalas de depresión, ansiedad y hostilidad del Brief Symptom Inventory (BSI). El análisis factorial confirmatorio apoyó una estructura de tres factores que presentó índices de confiabilidad y ajuste del modelo adecuados. El peor funcionamiento familiar se correlacionó con síntomas psicopatológicos, exceptuando la asociación entre depresión y comunicación disruptiva. Las mujeres revelaron niveles más altos de comunicación disruptiva, mientras que ser soltera se asoció con niveles más bajos de sentirse sobrepasada por las dificultades y comunicación disruptiva. La edad se asoció positivamente con sentirse abrumado por las dificultades y comunicación disruptiva. La versión mozambiqueña del SCORE‐15 mostró una buena validez factorial y confiabilidad y puede usarse en este contexto nacional sociocultural diverso. Puntos de implicación práctica SCORE‐15 es una medida sistémica de autoinforme para uso clínico rutinario e investigación sobre las relaciones familiares. En este estudio, SCORE‐15 mostró evidencia de confiabilidad y validez en Mozambique. Abstract : 摘要: 系统临床结果和常规评估(SCORE)‐15量表是一种广泛使用的工具，用于测量家庭功能的三个维度:优势和适应性，深陷困难，以及沟通中断。本研究评估了SCORE‐15在莫桑比克背景下的因素效度和信度。400名大学生完成了SCORE‐15量表和简明症状量表(BSI)的抑郁、焦虑和敌意分量表。验证性因素分析支持三因素结构，该结构提供了足够的模型拟合和可靠性指标。除了抑郁和沟通中断之间的联系外，家庭功能较差与心理病理症状相关。女性的沟通中断程度较高，而单身人士的深陷困难和沟通中断程度较低。年龄与深陷困难和沟通中断呈正相关。莫桑比克版本的SCORE‐15具有良好的因素效度和信度，可以在这个国家多元的社会文化背景下使用。 对从业者的启示 SCORE‐15是一种系统的自我报告测量方法，用于日常临床应用和家庭关系研究。 在本研究中，SCORE‐15在莫桑比克显示了信度和效度。